Incorporando tecnologias 3d a tv digital e interativa: um estudo de estratégias de integração baseadas no middleware ginga - Souza, Daniel Faustino Lacerda de (2010)
Recently, Brazil has defined its Digital Television standard. One of news in this model is the digitization of content transmitted by the broadcasters, which enables the convergence of applications and Internet services in interactive services for TV. In this sense, middleware for TV is the software which supports the implementation of such applications. The integration of 3D technologies in Digital Television environments extends the possibilities of interactivity and entertainment. Thus, the use of this technology can expand the range of research and business opportunities within the Interactive TV area. This work presents an architecture to support the execution of 3D applications on Digital Television environments. This architecture is based on DTV Brazilian middleware: Ginga. In this work are discussed strategies for integration of 3D technologies through execution and presentation environments of Ginga. Besides the definition of the architecture, this work presents a proof of concept for the new model presented as well as a performance analysis of the proposed solutions. Finally, a comparison is made between the solutions developed in order to determine which strategy is more feasible.